The rectus abdominis flap for perineal wounds. - Shukla, H. S. (Royal College of Surgeons of England, 1984)
The use of an inferiorly based rectus abdominis myocutaneous flap taken through the pelvis is described. It provides rapid healing of large perineal wounds following excision of advanced perineal malignancy or rectal excision in association with radiotherapy. Two cases were completely satisfactory, but the flap was lost in the third case because of delayed venous thrombosis. It is recommended that the rectus muscle below the entry of the inferior epigastric artery is not completely divided to prevent kinking of the vessels.